Under-Two Children Hunger Levels in Indonesia - Rita Diana; Yuliana Livi Andam Putri (Faculty of Medicine Universitas Padjadjaran, 2022)
Objective: To analyze the hunger level of toddlers under 2 years old using the Under-two Children Hunger Index (CHI). Methods: This study used secondary data from the Indonesian Basic Health Survey 2018. This study focused on the development of measurement for under-two children hunger index (CHI) using six indicators of the prevalence of chronic energy deficiency in pregnant women; the prevalence of risk height of pregnant women; the prevalence of under-two children who never being breastfeed; the prevalence of malnutrition for under-two children; the prevalence of wasting for under-two children; and the prevalence of stunting for under-two children. These six indicators were weighted differently and were calculated using the Principal Component Analysis (PCA) method.Results: The calculation of CHI using loading factors as weighted indicators has a higher precision with the percentage of 94.12 percent. With a 2018 CHI score of 46.40, Indonesia is at a serious CHI level. From the 34 provinces in Indonesia, 47.06% of provinces are at an extremely alarming level, 8.82% are at an alarming level, 17.65% are at a serious level, 17.65% are at a moderate level, and 8.82% are at a low level. Efforts can be performed by the government to increase the CHI based on the 6 indicators mentioned above.Conclusion: Based on this analysis, 25 provinces need attention in terms of the CHI level with six, three, and sixteen provinces suffered from a serious, alarming, and extremely alarming levels of CHI, respectively. Nevertheless, CHI is dynamic and should be updated annually to assess the province’s achievement in eradicating hunger. This time-series data is very important to evaluate government programs and programs to accelerate the eradication of under-two children's hunger should focus on the six indicators in this study.